Services Effect on Motivation Spirituality Healing Patiens in the Hospital Literature Review - Antina Atik; Yully Peristiowati; Agusta D. Ellina (GoAcademica Research & Publishing, 2021)
Healing motivation is a force that drives patients to take action to return to health. One way to increase the motivation of the patient's healing is to provide spiritual services, namely spiritual therapy. Many studies have shown that spiritual activity can increase a person's motivation and adaptation when experiencing pain as found in some of these studies on Spirituality from the results of existing research, by Karina Dinda Kinasih Aries Wahyuningsih, about the role of spiritual assistance in elderly patients in the Adult Inpatient Installation. The majority of Kediri Baptist Hospitals are good, namely 69 respondents (90%). The motivation for healing in elderly patients at the Adult Inpatient Installation of Baptist Hospital Kediri is a strong majority, namely 72 respondents (90%). Spiritual experiences experienced by patients studied by Fitriani Mailani with the title Spiritual Experiences in Chronic Kidney Disease undergoing Hemodialysis, where researchers explore spirituality in chronic kidney disease patients undergoing hemodialysis. The data was obtained through interviews with respondents, so that several themes were obtained, namely getting closer to God, support from the closest people, having high hopes for recovery, and accepting sincerely the illness they suffered, and having high hopes for recovery, such as trying non-medical treatment, believing miraculously and always pray for healing. The difference between spirituality and religiosity nursing problems in type-2 diabetes mellitus patients is directed at how nurses understand the concepts of spirituality and religiosity. Research by Ilhamsyah who looked at the relationship between the implementation of spiritual nursing and the spiritual satisfaction of hospital patients showed a significant relationship between the implementation of spiritual nursing and the spiritual satisfaction of patients with a significance level of P = 0.033. And several other studies say that the healing rate for patients with spiritual/spiritual assistance is quite high, so it is very important for hospitals to provide and determine the existence of spiritual assistance teams from various interfaith religions to provide motivation and spiritual needs of patients in accordance with the rights and obligations obtained in hospital services.